LncRNA DGCR5 Isoform-1 Silencing Suppresses the Malignant Phenotype of Clear Cell Renal Cell Carcinoma via miR-211-5p/Snail Signal Axis - Zhong, Guang-Xin; Luo, Dan; Fan, Yi-jun; Wang, Jue; Liu, Bing-Qiang; Xu, Zhong-Hua; Zhang, Xiang (Frontiers in Cell and Developmental Biology, 2021)
Long non-coding RNAs (lncRNAs) play important roles during the initiation and progression of cancer. We identified DiGeorge Syndrome Critical Region Gene 5 (DGCR5) as a ccRCC cancer and lineage specific lncRNA. Agarose gel electrophoresis analysis and sanger sequencing verified two main isoforms of DGCR5 in ccRCC patient tissues and cell lines. Quantitative polymerase chain reaction (qPCR) further demonstrated that expression level of DGCR5 major isoform (isoform-1) was higher in ccRCC tissues than that in papillary/chromophobe RCC and other multiple solid malignant tumors. We investigated the biological functions of DGCR5 isoform-1 in ccRCC and showed that DGCR5 isoform-1 exerts a tumor-promoting effect in ccRCC. DGCR5 isoform-1 was localized in cytoplasm and shared the same binding sequence to the tumor-suppressive miR-211-5p with Epithelial-to-Mesenchymal Transition (EMT) key component SNAI. Furthermore, cellular and molecular experiments demonstrated that DGCR5 isoform-1 could sequester miR-211-5p, leading to the elevation of Snail protein and down-regulation of its downstream targets, and further promoting ccRCC cell proliferation and migration. Thus, our study indicates that DGCR5 isoform-1 could contribute to ccRCC progression by sponging miR-211-5p through regulating the expression of Snail protein and could serve as a reliable diagnostic biomarker in ccRCC.